'Before I fought ideology, not money': Věra Chytilová and the 1990s transformation of Czech cinema culture. Issue 1 (2nd January 2019) - Bláhová, Jindřiška
ABSTRACT: The 1990s are perceived as a low creative point in Věra Chytilová's career and a far cry from her celebrated 1960s and 1970s films. While these were the focus of scholarly interest as rich landscape from which claims about gender-dynamics, cinema and authorial position under state-socialism can be gaged, her post-1989 body of work and her position within the transforming film culture attracted considerably less critical attention. Shifting focus from state-socialism, feminism and solely textual readings of her films, this essay examines '1990s Chytilová' as a filmmaker in transition and a political activist. First, it explores her opposition to privatization of Barrandov Film Studios and identifies some of the discourses of privatization that gave the economic processes its socio-cultural meaning. Second, it looks at her films Dědictví and Pasti, pasti, pastičky in their production context arguing that they are best understood as a reflection of her adaptability to new conditions and an extension of her engagement in politics. In doing so, the essay thus reorients perception of Chytilová's 1990s films and her development as a director. Moreover, it contributes to the understanding of privatization by shedding new light on the cinematic dimensions of the post-communist shift to capitalist democracy.